Sociological Aspects of Multicultural Islamic Religious Education - Huda , Miftahul (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
This writing aims to analyze the sociological aspects of multicultural Islamic religious education. Multicultural Islamic religious education is a solution to the plurality of Indonesian society in accordance with the democratic principles adopted by the Indonesian nation. Multicultural Islamic religious education is an important aspect in building the nation's next generation. Sociological aspects in multicultural Islamic religious education are fundamentally reflected by the existence of conducive cooperation between Islamic religious education in the family, school and community environment, good educational control will be realized. In a sociological context, the family is the first and foremost institution known to children. In this case, his parents are the first to be known and provide educational values. Then the school environment, the school at this time is a need for everyone to get an education from school. Schools in this case have two important aspects, namely individual aspects and social aspects. On the one hand, schools are tasked with influencing and creating conditions that allow optimal development. Furthermore, the community environment, a diverse society such as in Indonesia often creates the potential for friction or even conflict. Therefore, differences are a necessity in a pluralistic society. Differences must be accepted as a necessity. Such acceptance will lead to people's attitudes that can accept existing differences. This is what will produce students who have good morals, who will not only make their parents and teachers proud, but also the community as users of educational outcomes.